Contribution of Genetic Causes in Ear Vestibular Disorders - Y Lotfi; M Shaabani; A Navaei Lavasani (Journal of Paramedical Science and Rehabilitation)
Purpose:Vestibular disorders such as deafness are associated with heterogeneous genetic patterns and multifactorial hereditary transmission methods. Improvement in the field of genetic sequencing has provided evidence of familial classification in vestibular disorders and is the beginning for revealing the genetic causes and new treatment options, especially in Meniere’s disease and disorders associated with hearing loss. In this review, our aim is to present the recent findings in the field of effective genes in vestibular disorders and investigating the possible treatment of these disorders.Methods:In this review article, the words “genes and vestibular diseases” and genetic therapy had searched in ‘google scholar” and “science direct” and "PubMed" databases in the years 2000 to 2023.Results:After searching in Google Scholar, Science Direct and PubMed databases, new and related articles were collected and studied, and about 32 articles were used in this study.Conclusion:The application of molecular and gene therapy for the restoration and return of hearing and vestibular disorder is significant. The discovery of possible new treatments for the creation of new hair cells are important advances in science that will facilitate further studies towards biological treatment of inner ear diseases.